A Review of Classical and Rising Approaches the Extraction and Utilization of Marine Collagen - Cesia Deyanira Gutierrez-Canul; Luis Alfonso Can-Herrera; Emmanuel de Jesús Ramírez-Rivera; Witoon Prinyawiwatkul; Enrique Sauri-Duch; Victor Manuel Moo-Huchin; Emanuel Hernández-Núñez (BioTech)
This comprehensive review explores the extraction and utilization of marine collagen, a sustainable alternative to traditional mammalian sources. The review covers conventional extraction methods like acid and pepsin solubilization, highlighting their limitations and contributing to the search for improved efficiency and sustainability. It also delves into innovative extraction technologies, such as ultrasound-assisted extraction, deep eutectic solvents, and supercritical carbon dioxide, showing their potential to revolutionize the field. The significance of collagen hydrolysis in generating bioactive peptides with diverse functionalities is also discussed, emphasizing their potential applications in various sectors. By providing an analysis of marine collagen extraction and its implications, this review presents a perspective for leveraging this valuable bioresource, promoting a circular economy, and satisfying the increasing demand for high-quality collagen in diverse industries.